Emergency department utilization among children with Long COVID symptoms: a COVID-19 research consortium study - Pranav Bhimani; Adina Scheinfeld; Mangala Rajan (BMC, 2024)
Abstract Background and objectives Long COVID, characterized by persistent symptoms beyond the acute infection phase, remains poorly characterized in children. Our study aim is to determine if children who exhibit any symptoms/conditions associated with Long COVID after acute COVID-19 infection have higher Emergency Department (ED) utilization compared to those who do not exhibit these symptoms. Methods Data from the HealthJump ambulatory database from the COVID-19 Research Database Consortium was utilized to identify pediatric COVID-19 cases from March 2020 to May 2023. Long COVID cases were defined based on symptoms/conditions occurring 30-180 days after initial COVID diagnosis. Descriptive statistics and multivariable logistic regression models were used to model the relationship between Long COVID and child ED utilization. Results Out of 130,010 children diagnosed with COVID-19, 43,645 (33.6%) exhibited at least one Long COVID symptom/condition. Children with Long COVID symptoms/conditions had 152% higher odds (OR: 2.52, CI: 2.32-2.73) of ED visits, while those with specific symptoms including "chest pain" had 255% higher odds (AOR: 3.55, CI: 2.73-4.54) and "fluid and electrolyte disturbances" had 229% higher odds (AOR: 3.29, CI: 2.23-4.73) compared to those without those symptoms/conditions. Conclusion This study reveals that children with Long COVID symptoms had notably higher odds of ED visits, with chest pain, fluid imbalances, and generalized pain being most closely linked to such visits. This study highlights the burden of Long COVID on ED providers and underscores the importance of improved guidance for managing Long COVID symptoms in children.